Analisis Kepemimpinan Kepala Sekolah Dalam Peningkatan Prestasi Akademik IPAS Siswa di SD Inpres Parangrea Kecamatan Bajeng Kabupaten Gowa - Mukarramah, Mukarramah; Yunus, Muh; Iskandar, Arifuddin (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the leadership of school principals in improving the academic achievement of IPAS at SD Inpres Parangrea, Bajeng District, Gowa Regency. This research is a qualitative research with a descriptive approach. The subjects in this study are coaching supervisors, school principals, two low-grade teachers and 2 high-grade teachers. The data collection techniques in this study use interviews, observations, and documentation while the data analysis techniques used include data reduction, data presentation, and conclusion drawn/verification. The results of the study show that 1) The leadership of the principal at SD Inpres Parangrea has a very important role in improving the academic achievement of IPAS. The principal has carried out various strategies, ranging from the formulation of vision and mission, management of educational programs, teacher competency development, to innovation in learning. However, there are still several aspects that need to be improved, such as increasing teacher involvement in competency development programs, optimizing learning facilities, and more effective motivation strategies for students. The overall results of this study show that although the leadership of the principal has shown good development, there are still several areas that need to be improved so that the results achieved are more optimal, 2) The leadership of the principal at SD Inpres Parangrea has a diverse impact on the improvement of IPAS academic achievement. Several aspects such as a conducive academic culture, student learning discipline, and learning motivation have shown a positive impact, although there is still room for improvement in aspects of learning facilities and learning innovation. A comfortable learning environment has also been successfully created, although more attention needs to be paid to physical elements such as classrooms and green areas. Evaluation and learning outcomes show that the principal's efforts in supervising learning are good enough, but there is still a need for improvement in analyzing the evaluation results for more comprehensive improvement.